The exchange-traded funds manual - Gastineau, Gary L. (Hoboken, N.J. : Wiley, 2010)
"Full coverage of ETF investments from an expert in the field The initial edition of Gary Gastineau's The Exchange-Traded Fund Manual was one of the first books to describe and analyze ETFs. It made the case for the superiority of the structure of investor-friendly ETFs over mutual funds and helped investors select better funds among the ETFs available. With this new edition, Gastineau provides comprehensive information on the latest developments in ETF structures, new portfolio variety, and new trading methods. With a realistic evaluation of today's indexes, Gastineau offers insights on actively managed ETFs, improved index funds, and fund and advisor selection. Discusses how to incorporate ETFs into an investment plan. Offers updated coverage of new ETFs, including full-function actively managed ETFs, and a valuable chapter on trading ETFs. Written by the leading authority on exchange traded funds. Exchange-traded funds offer you diversification and participation in markets and investment strategies that have not been available to most investors. If you want to understand how to use ETFs effectively, the Second Edition of The Exchanged-Traded Fund Manual can show you how."--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Exchange traded funds; Stock index futures; Electronic books